A new concept for tuning design weights in survey sampling : jackknifing in theory and practice - Singh, Sarjinder, 1963-; Sedory, Stephen A., 1950-; Rueda Garcia, Maria del Mar; Arcos Cebrian, Antonio; Arnab, Raghunath (Academic Press, 2015)
A New Concept for Tuning Design Weights in Survey Sampling: Jackknifing in Theory and Practice introduces the new concept of tuning design weights in survey sampling by presenting three concepts: calibration, jackknifing, and imputing where needed. This new methodology allows survey statisticians to develop statistical software for analyzing data in a more precisely and friendly way than with existing techniques.